The New Order and Indonesian Islam Politics - Masykur Hakim (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2016)
Snouck Hurgronje, the advisor of Government of Netherland in Indonesia observed that Islam could be seen from two aspects: ritual and politic. “Give the full freedom to the Indonesian Muslims to conduct their religious doctrines related to the spiritual aspects, and do not give them the full freedom related the political aspects,” his suggestions at the time to the General Governor of Netherland to Indonesia. His view hence inspired the future leaders of Indonesia, Soekarno and Soeharto, particularly in the New Order under the President Soeharto. In the beginnings of his power he freed from the prisons the Masyumi figures, but did not permit to this Muslim organizations to rebirth; he forced all Islamic political parties to merger under one party, the PPP; he forced all political parties and mass organizations to use Pancasila as sole basic; he build hundreds of mosques every month; he supported the formation of ICMI (Association for Indonesian Muslim Intellectuals); he hesitated to capture and sent the prisons who criticized vocally all his policies, and this sad condition goes to continue till more than 30 years of his power. The time of big mutiny come to real condition following the all university students entire the archipelago came down to the streets and demanded Soeharto to resign, or they forced him to come down, and finally the fall of his power happened in 1998 with the sad ending, and it is the logical consequence of his politicization of Islam.